Effect of zinc on boar sperm liquid storage - Marini, Patricia; Fernández Beato, Luciana; Cane, Fernando; Teijeiro, Juan Manuel (Frontiers in Veterinary Science, 2023)
Storage and transport of liquid boar sperm for artificial insemination (AI) requires the addition of solutions called extenders, which increase the volume of the ejaculate and help preserve its functional characteristics. Yet, the quality of sperm decreases over time primarily due to the increased production of reactive oxygen species (ROS) that damage the plasma membrane. Many commercial extenders are supplemented with additives that mitigate this effect. In semen, zinc is supplied at high concentration on the seminal plasma and helps protect the plasma membrane of sperm. However, zinc in the seminal plasma is diluted and chelated upon addition of extenders for storage, potentially reducing its antioxidant effect. Here we characterize viability, motility, mitochondrial activity, DNA integrity and ROS content of boar sperm diluted with Sus (Medi Nova, Italy) extender supplemented with different concentrations of ZnCl2, at intervals after dilution during 3 days. The ability of sperm supplemented with 2 mM ZnCl2 to fertilize oocytes in vivo of was also tested. Sperm viability was over 82% for all treatments. Mitochondrial integrity analysis, measured by Cytochrome c activity, indicated a protector effect of Zn, noted as a reduced number of sperm with extensive loss of mitochondrial activity. Acrosomal integrity was improved by treatment with all concentrations of ZnCl2 tested. Sperm kinematics were affected by treatment with ZnCl2, showing higher percentage of progressive and rapid sperm in doses supplemented with 2mM ZnCl2. ROS levels and chromatin integrity did not show differences between ZnCl2-supplemented doses and the control. Fertilization rate, total number, live, still born and mummified piglets did not change when sperm were diluted with extender containing 2 mM ZnCl2. The presented characterization indicates that Zn addition to Sus extender have a protective effect on mitochondrial sheath and acrosomal membranes; and provides the basis for further studies aimed to optimize sperm performance in AI